Quality of life in heart failure patients undergoing hybrid comprehensive telerehabilitation versus usual care results of TELEREH-HF randomized clinical trial. (25th November 2020) - Piotrowicz, E; Mierzynska, A; Pencina, M; Opolski, G; Zareba, W; Banach, M; Kowalik, I; Orzechowski, P; Szalewska, D; Pluta, S; Irzmanski, R; Glowczynska, R; et al.
Abstract: Background: Heart failure (HF) is a clinical syndrome associated with physical capacity impairment and poor quality of life (QoL). The hybrid comprehensive telerehabilitation (HCTR) consisting of telecare, telerehabilitation and homemonitoring of implantable devices might be an option to improve QoL. Purpose to investigate the influence of HCTR on various facets of QoL in HF pts in comparison to usual care (UC). Methods: The present analysis formed part of TELEREH-HF multicenter, randomized trial that enrolled 850 HF pts (NYHA I-III, LVEF≤40%). Patients were randomized 1:1 to HCTR plus UC or UC. Patients underwent either an HCTR (1 week in hospital and 8 weeks at home) or UC with observation. The psychology telecare had a form of supportive psychotherapy via phone. The Short Form 36 Questionnaire was used to assess QoL. Measurements were made before and after intervention/observation. Results: HCTR group showed significant improvement in overall QoL, physical domain, and 4 areas of QoL (physical functioning [PF], role functioning related to physical state, general health, vitality). A significant positive change in QoL in UC group was observed in vitality and social functioning. There were significant differences in QoL after intervention/observation between groups. Results showed higher improvement in HCTR for overall QoL, physical domain and 3 areas of QoL (PF, role functioning related to physical state and bodily pain [BP]), Table 1. Conclusion: In comparison to UC, HCTR resulted in significant improvement in overall QoL, physical domain and 3 specific areas of QoL: PF, role functioning related to physical state and BP. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): National Centre for Research and Development, Warsaw, Poland